Health tracker: data acquisition and analysis for monitoring health trends and assessing disease risk - Alzaleq, Du'a; Alkhushayni, Suboh; FitzGerald, Austin (International Journal of Engineering and Technology, 2021)
This paper describes HealthTracker, a mobile health application to record, store, display, and analyze personal health data. This application allows an individual to log several types of data encompassing their personal health. HealthTracker serves as a model for both a recording and a recommending system. Its goal is to serve as a bridge for future personal health systems to build from. A personâ€™s health information is displayed in an easy-to-understand manner but is also practical for medical professionals. Users should find the system useful and effective no matter if they use it simply or extensively. Currently, the system serves as a prototype for determining the practical applications for smart health systems running on mobile platforms.Â Â